Розробка платформи для моніторингу офісних пристроїв в локальній мережі з використанням хмарних технологій - Кулініч, А. О. (ХНУРЕ, 2024)
This article is devoted to the advantages of remote management of office equipment. In this context, it is important to consider the potential and benefits of creating a platform for monitoring and managing office equipment. Such applications can become an integral part of the modern office environment, allowing businesses to maintain efficiency and productivity. The article also emphasizes the advantages of cloud technologies. Providing centralized management from the cloud allows you to effectively monitor and manage all devices in the local network from one place. This simplifies the management process and provides a single point of access to all necessary tools.
Keywords: моніторинг офісних пристроїв; використання хмарних технологій